Performance of Bangladesh indigenous rice in a weed infested field and separation of allelopathy from resource competition. Issue 2 (23rd May 2019) - Masum, Sheikh Muhammad; Hossain, Mohammad Amzad; Akamine, Hikaru; Sakagami, Jun‐Ichi; Ishii, Takahiro; Nakamura, Ichiro; Asaduzzaman, Md.; Bhowmik, Prasanta Chitta
Abstract : This study aimed to identify the potential allelopathic indigenous rice ( Oryza sativa L. ssp. indica ) varieties from Bangladesh using a performance study in a weed‐infested field and to assess the extent of allelopathic interference relative to resource competition in a glasshouse experiment. Six varieties – namely, "Boterswar, " "Goria, " "Biron" and "Kartiksail" as the most allelopathic, "Hashikolmi" as weakly allelopathic and "Holoi" as nonallelopathic – were raised following a nonweed control method. The infestation levels of weed species were calculated using Simpson's Diversity Index (SDI), which ranged from 0.2 to 0.56. However, a significant correlation coefficient (0.87, P < 0.001) was obtained from these field data compared with the root inhibition percentage from the laboratory bioassay, and the "Boterswar" variety was the most allelopathic. The interactions between the allelopathic variety "Boterswar, " weakly allelopathic variety "Hashikolmi" and Echinochloa oryzicola via a target (rice)‐adjacent ( E. oryzicola ) cogrowth culture were determined in a hydroponic arrangement. The relative competitive intensity (RCI) and the relative neighbor effect (RNE) values showed that the crop–weed interaction was facilitation for "Boterswar" and competition for "Hashikolmi" and E. oryzicola in rice/ E. oryzicola cogrowth cultures. The allelopathic effects of "Boterswar" were much higher than the resource competition in rice/ E. oryzicola cogrowth cultures. The converse was observed for "Hashikolmi." Moreover, the mineral content of E. oryzicola was severely affected by "Boterswar"/ E. oryzicola cogrowth cultures' exudate solution. Therefore, the allelopathic potential of "Boterswar" variety might be useful for developing the weed‐suppressing capacity of rice, which will likely have a significant influence on paddy weed control.